Employees' perception of quality of work life: a case study. (26th May 2021) - Sharma, Shuchi
The purpose of this research is to investigate the factors which affect quality of work life (QWL) in organisations and to find out if there is any difference in the perception levels of employees working in the public sector and private sector. The study used a structured questionnaire to collect and analyse employees' perceptions of their quality of work life and how QWL is influenced by job satisfaction, morale and motivation, employee commitment and involvement, equitable compensation and benefits, immediate opportunities for using abilities at work, opportunities for training, development and continued growth, communication and relationship with supervisors, workload and working conditions and by work and family life factors. The findings indicate that all these factors affect the perceived quality of work life of the employees and that there is no significant difference in the perception of employees in public sector and the employees in the private sector. The research offers insights towards implementing suitable solutions for encouragement and enhancement of employee performance.